DECISION SUPPORT SYSTEM FOR OPTIMIZATION OF WASTE UTILIZATION OF PALM OILMILL SOLID WASTE (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACT  The objective of this research was to develop a Decision Support System (DSS) for optimization of waste utilization of palm oil mill waste. The waste studied here focused on one that can be used by the oil palm industry, namely empty fruit bunch (EFB). The computerized model of decision support system for optimization of EFB utilization developed was called PW Optima 1.0. Goal  Programming (GP) combined with Analytical Hierarchy Process (AHP) were used for the optimization. Priority of several goals in the GP was determined by the AHP method. That goal targets of optimization of EFB utilization were an affordable cost, a minimize level of environmental pollution and maximum benefit. This decision support system model was verified by using real cases and showed promising results.  Keywords : decision support system, optimization, empty fruit bunch, goal programming, analytical hierarchy process